2002
DOI: 10.1097/00043426-200208000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Microalbuminuria in Children With Sickle Cell Anemia

Abstract: Microalbuminuria is strongly and directly related to age and strongly and inversely related to hemoglobin levels. Identification of risk factors for microalbuminuria may allow earlier intervention to prevent renal complications in patients with sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
47
5
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 12 publications
23
47
5
1
Order By: Relevance
“…In this study, we showed the prevalence of MA to be 16%, which is consistent with what has been previously reported by other authors [11][12][13][14][15][16][17]. To the best of our knowledge, this is the first study to specifically examine the relationship between blood pressure classification and microalbuminuria in children with sickle cell disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we showed the prevalence of MA to be 16%, which is consistent with what has been previously reported by other authors [11][12][13][14][15][16][17]. To the best of our knowledge, this is the first study to specifically examine the relationship between blood pressure classification and microalbuminuria in children with sickle cell disease.…”
Section: Discussionsupporting
confidence: 92%
“…Proteinuria, hypertension, and severe anemia have been shown to be predictors of ESRD in sickle cell nephropathy [1]. Studies in pediatric sickle cell patients have found the prevalence of abnormal urinary protein excretion to be as high as 28% (Table 4) [11][12][13][14][15][16][17]. In the largest of these studies, McKie et al studied 191 patients with Hb SS disease [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the findings reported by Unuigbe et al 26 in Benin City, Jones el al 15 in the USA and by Marsenic et al 29 and McBurney at al 30 among childern with sickle cell amaenia in the USA. They reported a positive correlation between microalbuminuria and age.…”
Section: Discussionsupporting
confidence: 90%
“…This causes medullary capillary congestion with extravasation of RBCs into the tubular lumen or rupture of the submucosal capillaries of the renal pelvis [1,50]. Macroscopic hematuria is a potentially life-threatening complication that may occur from renal papillary ne- Albuminuria Several studies have suggested that 16-27% of children with SCD have albuminuria [14,44,53,54].…”
Section: Hematuriamentioning
confidence: 99%